Outcomes of a Physician Survey on the Type, Progression, Assessment, and Treatment of Neurological Disease in Mucopolysaccharidoses - Scarpa,Maurizio (2018)
Abstract The mucopolysaccharidosis (MPS) disorders are a group of rare, inherited lysosomal storage disorders. In each of the 11 MPS (sub)types, deficiency in a specific lysosomal enzyme (1 of 11 identified enzymes) leads to accumulation of glycosaminoglycans, resulting in cell, tissue, and multi-organ dysfunction. There is great heterogeneity in the clinical manifestations both between and within each MPS type. Somatic signs and symptoms include short stature, coarse facial features, skeletal and joint abnormalities, cardiorespiratory dysfunction, hepatosplenomegaly, and vision and hearing problems. In addition, patients with MPS I, II, III, and VII can have significant neurological manifestations, including impaired cognitive, language, and speech abilities, behavioral abnormalities, sleep problems, and/or epileptic seizures. Hydrocephalus is a frequent finding in patients with MPS I, II, and VI. Spinal cord compression can develop in almost all MPS disorders. Effective management and development of therapies that target these neurological manifestations warrant a profound understanding of their pathophysiology and progression in the different MPS types and best practices for evaluation and treatment. In order to obtain expert opinion addressing these topics we performed an online survey among an international group of experts with extensive experience in managing and treating MPS disorders. The results of this survey provide important insights into the management of neurological manifestations of MPS in clinical practice and are a valuable addition to current evidence.